Differences in Keratometry Before and After Surgery Between Superior and Temporal Chevron Incision in Small Incision Cataract Surgery: Oral Presentation - Observational Study - Resident - I MADE SURYA DINAJAYA; Dr. dr. Mas Putrawati Triningrat, SpM(K); Dr. dr. Putu Yuliawati, SpM(K) (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Cataracts are the most common cases that cause blindness globally, where the lense was haze and characterized by decreased visual acuity and is reversible if optimal treatment is given. Examination before surgery is very important for outcome, where keratometry is one of the examinations before the surgery. Small incision cataract surgery (SICS) is one of cataract surgery technique, where a chevron incision is used in the superior or temporal regions. This study aims to determine which location is the best for an incision based on the results of keratometry. Methods : This research is an analytical observational study, bidirectional (prospective-retrospective) with a cohort study approach conducted at the eye polyclinic of Sanglah Hospital and Surya Husadha Hospital, Denpasar. The study sample consisted of 46 eyes which were divided into two groups, 23 superior and 23 temporal incision, then the results were compared between groups. Results : The results showed that the oldest age was the temporal incision group, which was 66.78±7.11. In the keratometry measurements, it was found that there were differences between the two groups, where the temporal incision resulted in smaller keratometric changes (p=<0.001). After analyzing the covariates, the temporal incision group still had smaller keratometry changes (p=<0.001) with astigmatism as an influential confounding factor. Meanwhile, post-op visual acuity was found in the temporal incision group which was better than the superior incision after analysis with covariates (p=0.002). Conclusion : This study showed that the temporal incision group gave lower keratometry results and better post- op visual acuity than the superior incision group.